Persistence of Salmonella Typhimurium LT2 in Soil Enhanced after Growth in Lettuce Medium - Fornefeld, Eva; Schierstaedt, Jasper; Jechalke, Sven; Grosch, Rita; Schikora, Adam; Smalla, Kornelia (Frontiers in Microbiology, 2017)
The persistence of Salmonella in the environment is influenced by a multitude of biotic and abiotic factors. In addition, their persistence can be influenced by preadaptation before their introduction into the environment. In order to study how preadaptation changes the survival of Salmonella in soil and therefore their potential to colonize the phytosphere, we developed a new medium based on lettuce material (lettuce medium, LM). Salmonella enterica serovar Typhimurium strain LT2 was used as a model for Salmonella in this study. LT2 was inoculated into soil microcosms after pregrowth in Luria Bertani (LB) medium or in LM. Survival of LT2 in soil was monitored over 56 days by plate counts and quantification of the Typhimurium-specific gene STM4497 using qPCR in total community DNA for which primers and TaqMan probe were designed in this study. Significantly enhanced persistence was observed for LT2 pregrown in LM compared to LT2 pregrown in LB, indicating a preadaptation effect. Surprisingly, no improved survival could be observed for S. Typhimurium strain 14028s and S. enterica serovar Senftenberg after pregrowth on LM. This indicates a high strain specificity of preadaptation. Results from previous studies suggested that biofilm formation could enhance the survival of human pathogens in various environments and might contribute to enhanced survival on plants. In vitro biofilm assays with several Salmonella strains revealed a strain-specific effect of LM on the biofilm formation. While LM significantly improved the biofilm formation of S. Senftenberg, the biofilm formation of LT2 was better in LB. This indicates that the better survival of LM-pregrown LT2 in soil was not linked to an improved ability to form biofilms but was likely due to other factors. Most importantly, this study showed that the medium used to pregrow Salmonella can influence its survival in soil and its biofilm formation which might influence the fate of Salmonella in soil.